CONCEPTS AND APPLICATIONS OF BANKING 4.0: SYSTEMATIC REVIEW AND PROPOSAL FOR A RESEARCH AGENDA - Nunes, Séfora; Fabiana Gohr, Cláudia; Costa Santos, Luciano (Brazilian Journal of Management and Innovation (Revista Brasileira de Gestão e Inovação), 2025)
Objective: The main objective is to analyze the particularities of Industry 4.0 (I4.0) concepts and technologies for banking/financial services (Banking 4.0 – B4.0). Specifically, the aim is to: (i) provide an overview of the literature on B4.0 technologies; (ii) propose a reference framework with B4.0 technologies and their applications in the context of the banking sector; (iii) present a research agenda for B4.0 considering the trends and gaps in the literature identified. Design/Method/Approach: The systematic literature review (SLR) method was adopted in the Web of Science and Scopus databases. Initially, 478 articles were identified, and after applying filters, a sample of 31 articles was obtained. Originality/relevance: The topic is important for B4.0 researchers, since there are few studies that address this theory and its technologies comprehensively using the SLR method. Main results/Conclusions: The topic is considered recent, with the first article published in 2019. In addition, it was found that the predominant methodological approaches in the research follow quantitative methods, and a smaller portion of the articles developed qualitative research. In terms of research application, there is still a concentration of studies in banks and the financial sector. Sixteen technologies associated with Banking 4.0 were identified, at which point definitions and examples of their application to the context under study were provided. Theoretical/methodological contributions/implications: the research contributed to the discussion and definition of B4.0, detection of new B4.0 technologies that can be applied in the financial sector and the proposal of a research agenda in the field.